Aprimoramento de catalisadores de ouro suportado em óxidos mistos de cério e ferro para a redução de NO por CO - Lage, Vitor Duarte (2018)
Catalytic processes are held to be streamlined pathways to cut down the emission of exhaustion gases, such as nitric oxide and carbon monoxide. In this regard, Cerium– iron mixed oxide supported gold catalysts for the reduction of NO by CO were prepared by deposition-precipitation and colloidal hydrosol. The gold catalysts prepared via deposition-precipitation displayed the best results for conversion of NO and CO and for selectivity towards N2. In fact, the hydrosol-prepared gold catalysts decreased the catalytic activity previously display by the mixed oxide support. This behavior was attributed to the presence of sulfur- and carbon containing species on the catalyst attested by TGA, TPD-He, DRIFTS and XPS analyses. For the gold catalysts prepared by deposition-precipitation, it was observed on the same set of analyses a hydroxyl-rich surface, a high cationic gold content, and a strong gold–support bonding. The increase in the low-temperature activity and selectivity towards N2 was mainly attributed to those three surface characteristics. Lastly, in regard of the tested pretreatments, the gold catalysts pretreated on oxygen flow displayed the best activity and stability results, yielding 100% of NO and 89% of CO with an N2 selectivity of 64% at 200 ºC. At 300 ºC, maximum yield for NO and CO, and maximum N2 selectivity were obtained.